Effects of tamoxifen on urinary incontinence: Case report and review of literature. Issue 34 (August 2017) - Hasanov, Elshad; Hasanov, Merve; Kuria, Issa M.; Hasanov, Rovshan; Rzazade, Reshad; Jonasch, Eric; Altundag, Kadri
Abstract: Rationale: Tamoxifen has been used in women with hormone receptor-positive breast cancer and has been shown to successfully reduce both recurrence and mortality. On the contrary, long-term use of tamoxifen has hormone-related urogenital side effects which decrease the quality of life of the patients. Patient concerns: In this case report, we present a breast cancer patient receiving tamoxifen who developed urinary incontinence; we discuss the effects of tamoxifen on urinary incontinence, which decreases quality of life of the patients who were evaluated in our clinic. Diagnoses: Breast cancer, urinary incontinence. Interventions: Temporarily discontinuing tamoxifen. Outcomes: Urinary incontinence resolved. Lessons: Based on the case we reported and literature, estrogen can cause a dose-dependent increase in incontinence, but more preclinical and clinical studies of both estrogen and SERMs are needed to support this notion; given the fact that some small-scale clinical studies have not proven a direct relationship between tamoxifen and urinary incontinence. We suggest that clinicians faced with the issue should temporarily stop usage of the drug once the complaint of urinary incontinence arises.